Lokalvalget 2019 Nye kommuner - nye valg? - Saglie, Jo; Segaard, Signe Bock; Christensen, Dag Arne (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2021)
"This anthology concerns the many local elections held throughout Norway on 9 September 2019. Based on voter surveys carried out after every local election since 1995, the ten chapters in this book explore a variety of election-related topics such as voting behaviour and election campaigns, as well as political participation and political trust between elections. It is at the municipal level that most citizens can influence policy, and what occurs at the local level often plays a vital role in people's daily lives. One of the objectives of this book is therefore to better understand how local democracy functions, both in and between elections. The 2019 local elections were marked by mobilization, protest, and high turnout, due to the focus on politically charged issues such as the toll roads, climate change, and municipal amalgamation. Amalgamation was not just a campaign issue, but a part of the institutional context; the 2019 elections took place in newly merged municipalities. This is therefore a dominant topic throughout this book. How citizens feel about municipal reform and its potential consequences, for example, is explored. Several chapters examine the significance of amalgamation on various aspects of local democracy: local party systems, turnout and voting behaviour, the parties' candidate selection, and representation in municipal councils. Taken as a whole, this anthology represents a status report on local democracy in the first election held in the merged municipalities. This book will be of interest to anyone following developments in local democracy in Norway, especially students, researchers, journalists, and politically active citizens."